2023
DOI: 10.1177/13594575231155267
|View full text |Cite|
|
Sign up to set email alerts
|

Music therapy for adolescents in a child welfare setting - a qualitative interview study

Abstract: In this article, we explore challenges and possibilities as expressed by adolescents who participated in music therapy in an out-of-home setting. Music activities they reported participating in include listening to music, songwriting, playing in a band, and performing. The study is based on qualitative research methodology where we ask the following research question: What do adolescents in a child welfare setting consider as challenges and possibilities when reflecting on their participation in music therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Previous research with children in mental health care shows that non-verbal musical dynamics and musical interaction can facilitate emotion regulation (Johns, 2018 ; Sannes, 2012 ). Dealing with complex emotions through music has also been highlighted by staff in child welfare as an advantage of music therapy in relation to children’s mental health (Krüger et al, 2018 ). Emotion regulation is also relevant in music therapy with children with trauma, helping facilitate new possibilities for action (Johns, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research with children in mental health care shows that non-verbal musical dynamics and musical interaction can facilitate emotion regulation (Johns, 2018 ; Sannes, 2012 ). Dealing with complex emotions through music has also been highlighted by staff in child welfare as an advantage of music therapy in relation to children’s mental health (Krüger et al, 2018 ). Emotion regulation is also relevant in music therapy with children with trauma, helping facilitate new possibilities for action (Johns, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Included studies (Armstrong-Heimsoth et al, 2020;Paul-Ward et al, 2014) This review found some evidence that arts-based therapies may help with the behaviour-related needs of children living in or leaving care (Abrahams & van Dooren, 2018). Furthermore, artsbased therapies may positively influence children and young people's evolving sense of identity development through making meaning of their complex and fractured family and relational life stories (Krüger et al, 2017;Krüger & Stige, 2015;Savage, 2020;Zanders, 2015). Although Abrahams and van Dooren's (2018) randomised controlled pilot study on a form of music therapy, MACT, in secure residential care is helpful to explore the potential benefits of this therapeutic approach, results must however be interpreted with caution given the very small sample size and the fact that all participants were diagnosed with ADHD, ADD, ODD and/or CD.…”
Section: Discussionmentioning
confidence: 99%
“…The reported benefits of arts-based therapies include the idea that creative self-expression has the potential to support purposeful personal reflection which can assist with attachment difficulties and the formulation of a stable identity (Krüger et al, 2017;Krüger & Stige, 2015;Savage, 2020;Zanders, 2015). This has particular relevance to children's developing sense of agency, security and belonging, all issues identified as of utmost importance for children and young people living in and leaving care (Schofield et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations